TINDAK TUTUR BAHASA DALAM GENDER DI SDK HARAPAN DENPASAR KELAS V - I Gede Neil Prajamukti Wardhana (Fakultas Bahasa Asing (FBA) Universitas Mahasaraswati Denpasar, 2019)
ABSTRACTSocial beings do not live alone, depend on other people and always need it. Yule (2016: 118) stated that the term of speech act used to describe the actions like “asking” “commanding” “asking question” or “giving information”. This research was descriptive analysis research that finding speech act and also related with gender by student and teacher in the class. The sample of this research was grade 5A SDK Harapan, Denpasar in the academic year 2017/2018. The method of collecting data of this research was qualitative approach in the study case and also by observation method to students and teacher in elementary school. Data that collected was written conversation and sentence by students and types of speech act in gender. The results of this research was finding conversation and sentence happened in the class and compatible types of speech act and related with gender. One of these results of in this research was “indah banget ini bu” in terms of compliments (Kuntjara, 2003). Based on these results of this research is needed the concern from the teacher and school in doing the speech act and also in gender happening in the class as well as school. Keywords: language, speech act and gender